33 "Striking Back Against Stroke". (16th September 2019) - Donaghy, Lisa; Morrison, Laura; Prendergast, Julie; Dolan, Eamon; O'Connor, Marie
Abstract: Background: 2 million brain cells die every minute increasing the risk of permanent brain damage, disability or death. Despite the fact that IV Thrombolysis and Thrombectomy are now the standard of care, optimal rates of door to needle times and door to decision times have not been managed to be achieved throughout Ireland. There is a gap between what we know and what we do. Treatment within a shorter time frame improves patient outcomes. Aim: To reduce door to decision time for Thrombectomy to <30minutes in conjunction with the National Thrombectomy Quality Improvement Programme. Methods: A Stroke Committee was set up consisting of a wider group of Stakeholders involved in FAST positive calls. A pre-audit of baseline times was conducted. Each step was mapped out in a process map and areas of delays were identified to reduce the overall KPI times. Delays and areas for change: 1. Pre-alert by ambulance ✓ Audit ✓ Education 2. Alerting the Stroke Team ✓ Audit time of referral ✓ Education with ED staff 3. Registration ✓ Pseudo MRN 4. IVC ✓ Nexiva Diffusics 5. Urgent INR ✓ Red "FAST Stroke" labels ✓ Education with laboratory staff 6. Equipment for transfer ✓ No cardiac monitoring for stable patient Results: Door to CT times reduced from 37minutes to 22 minutes (↓ 15minutes) Door to CTA time reduced from 35 minutes to 28 minutes (↓ 7minutes) Door to Thrombolysis reduced from 65 minutes to 30 minutes (↓ 35 minutes) CTA to time of contact Beaumont (↓ 5minutes) Door to decision re: Thrombectomy or not reduced from 166 minutes to 24.5 minutes (↓ 141.5 minutes) Conclusion: This is an ongoing process which continues to ultimately improve patient outcomes. "Time is Brain"